Perancangan Aplikasi Fusi Citra Pankromatik Dan Citra Multispektral Menerapkan Algoritma Wang Bovik - Benedikta Deliani Gea (STMIK Budi Darma, 2022)
The development of remote sensing technology offers convenience in mapping an area. This can be seen from the use of digital maps which are very often used for mapping an area. Currently, remote sensing satellite sensor systems can operate in multispectral mode and panchromatic mode simultaneously. Remote sensing satellites are capable of producing multispectral and panchromatic images with high spatial resolution, but the resulting panchromatic images have a higher spatial resolution than the multispectral images produced by these remote sensing satellites. This is the background for designing a multispectral image fusion application and a panchromatic image by applying Wang Bovik's algorithm method.To produce images that have high spatial resolution with low spatial resolution with panchromatic images with high spatial resolution so that an output image will be produced which has the advantages possessed by multispectral images and the advantages possessed by panchromatic images. To solve the problem of this image fusion application, the authors use an algorithm method wang bovik. This method is expected to be able to solve the problem of image fusion for image sharpening in image fusion applications. In this thesis, we will discuss how to create image fusion applications using the Brovey transformation method using the Visual Basic programming language. This application was built using Microsoft Visual Studio.net 2008 as an editor to edit the program.